2010
DOI: 10.11646/zootaxa.2470.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Palaearctic oak gallwasps galling oaks (Quercus) in the section Cerris: re-appraisal of generic limits, with descriptions of new genera and species (Hymenoptera: Cynipidae: Cynipini)

Abstract: We discuss the taxonomy of oak gallwasps (Hymenoptera: Cynipidae: Cynipini) whose lifecycle involves only Palaearctic oaks (Quercus subgen. Quercus) in the section Cerris. Recent phylogenetic reconstructions support a deep split between such Cerris-associated species in the genera Aphelonyx, Dryocosmus, Plagiotrochus, Neuroterus, Pseudoneuroterus and species and genera associated with oaks in the section Quercus sensu stricto. We reappraise the generic limits of the Cerris-associated genera, proposing new limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 1 publication
0
40
0
Order By: Relevance
“…One undescribed species of Plagiotrochus galling Q. (C.) glauca has been indicated from Taiwan (Melika et al 2010), but it has not yet been described. Although two species of Andricus have previously been described as gall inducers (Cynipini) on Cyclobalanopsis in Japan (Shinji 1940(Shinji , 1941, closer examination of their gall features (Yukawa and Masuda 1996) has suggested that these species are in fact inquiline gall wasps that have been erroneously assigned to the gall inducing wasps of the Cynipini.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One undescribed species of Plagiotrochus galling Q. (C.) glauca has been indicated from Taiwan (Melika et al 2010), but it has not yet been described. Although two species of Andricus have previously been described as gall inducers (Cynipini) on Cyclobalanopsis in Japan (Shinji 1940(Shinji , 1941, closer examination of their gall features (Yukawa and Masuda 1996) has suggested that these species are in fact inquiline gall wasps that have been erroneously assigned to the gall inducing wasps of the Cynipini.…”
Section: Discussionmentioning
confidence: 99%
“…Although the host plants of most species of Plagiotrochus are restricted to section Cerris (subgenus Quercus) oaks (Melika et al , 2010 ), given the widespread distribution of Cyclobalanopsis oak species in the country, it is possible that these cynipid wasps also induce galls on oak trees of this subgenus.…”
Section: Discussionmentioning
confidence: 99%
“…The terminology used to describe gallwasp morphology follows other recent cynipid studies (Melika 2006;Melika et al 2010;Liljeblad et al 2008). Abbreviations for fore wing venation follows Melika (2006), cuticular surface terminology follows that of Harris (1979).…”
Section: Morphological Descriptionsmentioning
confidence: 99%
“…Using a key to the Palearctic genera of Cynipini (Melika et al 2010), this new species falls into Dryocosmus. D. nanlingensis is uniquely characterized by the emergence of an adult of sexual generation in winter.…”
Section: Dryocosmus Nanlingensis Abe Ide and Odagirimentioning
confidence: 99%
“…D. nanlingensis falls into Dryocosmus when using a key to the Palearctic genera of oak gall wasps, Cynipini (Melika et al 2010). Cynipid heterogony is characterized by a strict regularity with respect to the timing and emergence of the sexual and asexual generations (Hebert 1987, Suomalainen et al 1987; the sexual generation adults typically emerge in the spring and their offspring emerge as the asexual generation from the following fall to early spring (Yukawa andMasuda 1996, Stone et al 2002).…”
mentioning
confidence: 99%